2015
DOI: 10.7150/thno.7976
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous Intramyocardial Delivery of Mesenchymal Stem Cells Induces Superior Improvement in Regional Left Ventricular Function Compared with Bone Marrow Mononuclear Cells in Porcine Myocardial Infarcted Heart

Abstract: Aim: To investigate the efficacy and feasibility of percutaneous intramyocardial injection of bone marrow mesenchymal stem cells (MSC) and autologous bone marrow-derived mononuclear cells (BMMNC) on cardiac functional improvement in porcine myocardial infarcted hearts. Methods and Results: Acute myocardial infarction (AMI) was induced in 22 minipigs by temporary balloon occlusion of the left anterior descending coronary artery for 60min.Two weeks post AMI, BMMNC (n = 7, 245 ± 98×106), MSC (n = 8, 56 ± 17×106),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 30 publications
0
26
0
Order By: Relevance
“…In a swine acute-MI model, Tao et al (352) found that autologous bone marrow-derived MSCs engrafted within the ischemic myocardium at week 3 but not at week 10 post-injection (352). Analogously, immunohistochemistry studies against In fact, an intravenous approach to cellular delivery has been to shown to result in insufficient MSC engraftment (150), and intramyocardial administration may be more superior to the intravenous or intracoronary routes (103).…”
Section: A Engraftment Differentiation and Fusionmentioning
confidence: 94%
“…In a swine acute-MI model, Tao et al (352) found that autologous bone marrow-derived MSCs engrafted within the ischemic myocardium at week 3 but not at week 10 post-injection (352). Analogously, immunohistochemistry studies against In fact, an intravenous approach to cellular delivery has been to shown to result in insufficient MSC engraftment (150), and intramyocardial administration may be more superior to the intravenous or intracoronary routes (103).…”
Section: A Engraftment Differentiation and Fusionmentioning
confidence: 94%
“…Stem cell transplantation has therapeutic effects on AMI [37, 38]. However, due to changes in the myocardial tissue environment after ischaemia, the function of the transplanted cells is restricted.…”
Section: Discussionmentioning
confidence: 99%
“…A previous meta-analysis of large animal models (such as pigs, dogs, and sheep) of MI indicated that the transplantation of BM-MSCs led to a significant improvement of left ventricle ejection fraction. In addition, a trend toward greater advantage in the case of administration of MSCs when compared with BM-MNCs was reported (32,33).…”
Section: Figmentioning
confidence: 97%